Demographics, radiological findings, and clinical outcomes of Klebsiella pneumonia vs. Non-Klebsiella pneumoniae pyogenic liver abscess: a systematic review and meta-analysis with trial sequential analysis - Chan, Kai Siang (2023)
Pyogenic liver abscess (PLA) is a common cause of hepatobiliary sepsis. Klebsiella pneumoniae (KP) is the most common organism causing PLA. Evidence is scarce on the demographics, radiological findings, and outcomes of KPPLA versus non-KPPLA (N-KPPLA). PubMed, Embase, The Cochrane Library, and Scopus were systematically searched until 14 May 2022 for studies comparing KPPLA and N-KPPLA. Exclusion criteria were single-arm studies. Primary outcomes were mortality (30-day/in-hospital) and metastatic complications. There were 16 studies, including 5127 patients (KPPLA n = 3305, N-KPPLA n = 1822). Patients with KPPLA were younger (mean difference: −2.04 years, p = 0.02). History of hepatobiliary disease (Odds ratio (OR) 0.30, 95% CI: 0.20, 0.46) and malignancy (OR 0.26, 95% CI: 0.16, 0.42) were less common in KPPLA. KPPLA was associated with lower incidence of multiple abscesses (OR 0.52, 95% CI: 0.35, 0.76, p < 0.001) and bilobar abscesses (OR 0.60, 95% CI: 0.49, 0.74, p < 0.001). KPPLA has higher overall metastatic complications (KPPLA 9.7% vs. N-KPPLA 4.8%, OR 3.16, 95% CI: 2.00, 4.99, p < 0.001), but lower mortality (KPPLA 3.9% vs. N-KPPLA 7.6%, OR 0.51, 95% CI: 0.34, 0.78, p < 0.001). Trial sequential analysis showed conclusive evidence that KPPLA has lower mortality than N-KPPLA. In conclusion, KPPLA has lower mortality than N-KPPLA.